(untitled) (Religious dialogue and cooperation, 2023)
Divine Revelation is rarely considered in its all-embracing importance. We find more often particularistic interpretations defined by certain traditions, confessions, and theoretical schools rooted in a certain historical period. Such approaches are valuable contributions as they offer a possible way to understand the world in a more-than-trivial fashion. Philosophical and theological developments based on particularistic traditions are also helpful because they show the power of genuine inspiration. Nevertheless, the problem of divine revelation cannot be confined to a particular tradition. The concept of revelation suggests that revelation as a basic concept rises above historical, cultural, and denominational forms and elevates human persons to a sphere where divine reality discloses an overarching design. In today’s world, where various traditions, religious forms, and denominations are becoming interconnected, it is essential to understand divine revelation in a way that is not distorted by various particularisms. In a few published works, I have repeatedly pointed out the essential feature of divine revelation as unrestricted newness. In the following text, I will argue that this newness comes to the fore as soon as we perceive revelation properly. Focusing on newness, we can reconsider particular narratives of divine revelation from the perspective of their renewing power leading to a global community of human beings. To achieve this, I emphasize the importance of spiritual practice, such as revelatory meditation, through which people of various backgrounds can think through their understandings of divine revelation. By doing so, we can open the possibility of finding a common theoretical praxis to mend the world.